A reliable fault detection algorithm for distribution network with DG resources - Pandey A.K.; Kishor N.; Mohanty S.R.; Samuel P. (My University, 2025)
The natural disaster though may have less probability, but their impact can be extreme. For instance, windstorms can result in not only single instantaneous impact, but on multiple locations in the power grid. In such situations, detection of faults in active distribution networks (ADNs), having integration of different types of distributed generation (DG) resources, further escalates the challenging task for existing conventional techniques. The reliability of existing detection schemes is further compromised in case of high impedance faults (HIFs). This paper presents a unified approach for reliable detection of both low-impedance and high-impedance faults, while maintaining the discrimination against non-fault events. In the proposed detection algorithm, the fault detection index is calculated using a newer version of empirical mode decomposition (EMD), i.e., improved complete ensemble EMD with adaptive noise (ICEEMDAN). The performance is demonstrated for detection of multiple faults occurrence at different locations in the ADN. It is shown that with selection of uniform threshold value for all the relays in the network, only the dedicated primary and back-up relays operate reliably at the time of fault conditions. The scheme exhibits accurate, fast and reliable operation as compared to available works in the literature. © 2023 Elsevier B.V.